International cooperation in tobacco control - شهاب, حسام حميد (Journal of Legal Sciences, 2021)
The Framework Convention on Tobacco Control is among the main agreements that dealt with the topic of tobacco control. In spite of the efforts made in this aspect by countries through the preparation and the speed of ratification, there are some obstacles that prevent the achievement of the objectives of the convention including the tobacco companies' pursuit of not   implementing the agreement in the necessary manner. In light of this, many countries and international organizations, foremost of which is the World Health Organization, have undertaken to overcome these obstacles. Among the efforts are those which are made in the framework of exchanging information, technical and specialized assistance, and mutual legal support between the actor…